Pengujian Fungsional Sistem Informasi Inventori Berbasis Web Menggunakan Standar ISO/IEC 29119 - Siti Maemunah; Latifah Chumai Roh; Chairul Anwar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The development of information technology encourages the use of web-based systems to support business processes, including inventory management in retail stores. An inventory information system plays an important role in helping store owners manage product data, stock levels, and categories efficiently. However, the developed system must be tested to ensure that all functionalities operate according to user requirements. This study aims to conduct functional testing on a web-based inventory information system using the ISO/IEC 29119 standard. The testing method applied is black-box testing by preparing Test Plan, Test Case, and Test Report documents based on the standard. The testing results indicate that most of the system’s main functions operate properly, although several functional defects were identified in certain modules. The implementation of ISO/IEC 29119 provides a structured and well-documented testing process that can be used as a basis for evaluating the quality of the store inventory system.